Anatomical components of cranial-mandibular joint complex. - Contreras, Andrea (2017)
Objective: Of this study is to describe, based on dissections of anatomical pieces, the anatomical components of the Craniomandibular Joint Complex (CMJC). Materials and Methods: Eighteen half-heads of anatomical preparations belonging to Venezuelan human adults, previously treated with 10% formaldehyde and preserved in Gerdex ® undiluted for 6 months, prior to manual practice, were used. Consequently, the elements were dissected following the protocol of the Faculty of Dentistry of the University of Los Andes and particularizing the anatomical pieces in order to broach the different nature of the elements that constitute the CMJC. Results: The anatomical dissection was able to contrast the referred from a theoretical point of view in relation to what can be evidenced in a surgical intervention, illustrating the anatomical content that it has in normal conditions. The elements of the CMJC mostly coincide remarkably with what is described in this research, therefore, the solid knowle